TRPing on Cell Swelling - TRPV4 Senses It - Toft-Bertelsen, Trine L.; MacAulay, Nanna (Frontiers in Immunology, 2021)
The transient receptor potential vanilloid 4 channel (TRPV4) is a non-selective cation channel that is widely expressed and activated by a range of stimuli. Amongst these, cell volume changes feature as a prominent regulator of TRPV4 activity with cell swelling leading to channel activation. In experimental settings based on abrupt introduction of large osmotic gradients, TRPV4 activation requires co-expression of an aquaporin (AQP) to facilitate such cell swelling. However, TRPV4 readily responds to cell volume increase irrespectively of the molecular mechanism underlying the cell swelling and can, as such, be considered a sensor of increased cell volume. In this review, we will discuss the proposed events underlying the molecular coupling from cell swelling to channel activation and present the evidence of direct versus indirect swelling-activation of TRPV4. With this summary of the current knowledge of TRPV4 and its ability to sense cell volume changes, we hope to stimulate further experimental efforts in this area of research to clarify TRPV4’s role in physiology and pathophysiology.